MIR137 is an androgen regulated repressor of an extended network of transcriptional coregulators - Nilsson, Emeli M.; Laursen, Kristian B.; Whitchurch, Jonathan; McWilliam, Andrew; Ødum, Niels; Persson, Jenny L.; Heery, David M.; Gudas, Lorraine G.; Mongan, Nigel P. (Impact Journals, 2015)
Androgens and the androgen receptor (AR) play crucial roles in male development and the pathogenesis and progression of prostate cancer (PCa). The AR functions as a ligand dependent transcription factor which recruits multiple enzymatically distinct epigenetic coregulators to facilitate transcriptional regulation in response to androgens. Over-expression of AR coregulators is implicated in cancer. We have shown that over-expression of KDM1A, an AR coregulator, contributes to PCa recurrence by promoting VEGFA expression. However the mechanism(s) whereby AR coregulators are increased in PCa remain poorly understood. In this study we show that the microRNA hsa-miR-137 (miR137) tumor suppressor regulates expression of an extended network of transcriptional coregulators including KDM1A/LSD1/AOF1, KDM2A/JHDM1A/FBXL11, KDM4A/JMJD2A, KDM5B JARID1B/PLU1, KDM7A/JHDM1D/PHF8, MED1/TRAP220/DRIP205 and NCoA2/SRC2/TIF2. We show that expression of miR137 is increased by androgen in LnCaP androgen PCa responsive cells and that the miR137 locus is epigenetically silenced in androgen LnCaP:C4-2 and PC3 independent PCa cells. In addition, we found that restoration of miR137 expression down-regulates expression of VEGFA, an AR target gene, which suggests a role of miR137 loss also in cancer angiogenesis. Finally we show functional inhibition of mIR137 function enhanced androgen induction of PSA/KLK3 expression. Our data indicate that miR137 functions as an androgen regulated suppressor of androgen signaling by modulating expression of an extended network of transcriptional coregulators. Therefore, we propose that epigenetic silencing of miR137 is an important event in promoting androgen signaling during prostate carcinogenesis and progression.